Trade-offs between agricultural production and ecosystem services under different land management scenarios in the Loess Plateau of China - Jing Jiang; Hui Zhao; Jun Zhang; Bo Dong (Scientific Reports)
Abstract Land management practices play a crucial role in balancing agricultural production and ecosystem services. This study evaluated the trade-offs between provisioning ecosystem services (crop yields) and other key ecosystem services including regulating services (water yield, soil conservation, carbon sequestration) and supporting services (biodiversity) under three land management scenarios in the Loess Plateau of China. An integrated assessment framework combining biophysical models, economic valuation, and trade-off analysis was applied. The results showed significant trade-offs between provisioning ecosystem services (agricultural production) and regulating and supporting ecosystem services (water yield, soil conservation, carbon sequestration, and biodiversity). The ecological restoration scenario maximized regulating and supporting services but reduced agricultural output by 15%, while the sustainable intensification scenario increased agricultural production by 15% with moderate ecosystem service provision. The business-as-usual scenario showed intermediate performance for both. Trade-offs were driven by land use intensity, landscape configuration, biogeochemical cycles, and hydrological processes. We propose strategies including sustainable intensification practices, landscape multifunctionality enhancement, ecosystem-based adaptation, participatory land-use planning, and improved monitoring systems. These findings highlight the need for integrated approaches that balance food production and environmental sustainability, providing insights for land management policies aligned with UN Sustainable Development Goals.